2022
DOI: 10.3389/fphy.2022.1085789
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of diversity, equity, inclusion, and justice in the earth system sciences

Abstract: Institutions’ motivations for pursuing diversity, equity, inclusion and justice (DEIJ) often center on the benefits to the organization, an argument known as the business case for diversity in which diverse teams are more creative, set high bars for research, and produce ideas that are more innovative than those produced by homogeneous groups. As the sole motivation for DEIJ efforts, the business case is flawed and does not address the harmful workplaces many marginalized scholars encounter. Institutions can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In essence, although universities are implementing DEI policies because of the academic and professional advantages they bring, they do not always consider the ethical aspect (Burt et al, 2022), when clearly it is required. More research is therefore still needed to guide the development and implementation of effective DEI policies and practices in higher education.…”
Section: The Role Of Research In Advancing Diversity Equity and Inclu...mentioning
confidence: 99%
“…In essence, although universities are implementing DEI policies because of the academic and professional advantages they bring, they do not always consider the ethical aspect (Burt et al, 2022), when clearly it is required. More research is therefore still needed to guide the development and implementation of effective DEI policies and practices in higher education.…”
Section: The Role Of Research In Advancing Diversity Equity and Inclu...mentioning
confidence: 99%
“…Academic institutions and organizations have an ethical obligation toward pursuing diversity, equity, inclusion, and justice (DEIJ) (Burt et al, 2022). The participation of underrepresented/marginalized groups in academia is generally low, which is primarily driven by certain STEM fields (Li and Koedel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While the case can be made that productivity and results improve with a diverse workforce, this alone does not have to motivate us into action. Burt et al (2022) showed that the "business case" for diversity is misaligned with current attitudes of young professionals in both the Earth and space sciences and more broadly across science and engineering, in general. Rather than seeking only the benefits that diversification can yield for (primarily white, male) institutions, many are motivated by their interest in equity and inclusion (Haacker et al, 2022).…”
Section: Introduction 1diverse Teams Lead To Better Space Physicsmentioning
confidence: 99%